Evolving liver transplantation in Pakistan: Future challenges. (October 2022) - Dogar, Abdul Wahab; Ullah, Kaleem; Ochani, Sidhant; Ahmad, Hafiz Bilal
Abstract: Liver transplantation is a life-saving procedure that started in the early 60s. Initially, it struggled with multiple failed attempts but later it progressed and emerged as a gold standard procedure for liver failure secondary to various etiologies. In the first two decades, it faced various challenges like peri and post-operative care management, the quality of graft, optimal immunosuppressant use, and recipient selection criteria. Because of these challenges, the 1-year survival remained below 30% initially. Liver transplantation flourished tremendously over time due to advancements in organ preservation techniques, immunosuppressive therapies, and a better understanding of immunology. The invention of calcineurin inhibitors changed the dynamics of immunosuppressive therapies altogether. The donor organ shortage remains the leading challenge, Deceased donor transplantation activities have not yet started here due to various socio-cultural, and religious resistance. The majority population of the country is underprivileged and faces financial issues to afford the costly liver transplant procedure. The other challenges include the emerging NASH and obesity epidemics. The prevalence of viral hepatitis has not decreased in the country despite advancements in antiviral therapies and vaccine availability against hepatitis B. The local transplant community needs to overcome the limitation of organ supply through various donor expansion approaches. Although it may seem difficult to address all these challenges, still, the transplant community and health authorities need to find an effective way to sort out all these challenges.